An Empirical Analysis of Influencing Factors on IPO Underpricing Evidence from China - Han, Wenran (2020)
As the most important part of capital market, stock market has played a role in financing, allocating resources, and serving the real economy. As the start of stock, IPO pricing has a great impact on the trading price of stocks in the secondary market. Since IPO underpricing was discovered and confirmed in the 1970s, a large number of experts have studied the factors of IP0 underpricing based on different theories such as efficient market hypothesis and behavioral finance theory. Compared with developed capital markets, IPO underpricing is particularly severe in China, which has also attracted the attention of many scholars. Taking 2471 IPOs listed from 2005 to 2019 as samples, this paper investigates the factors of IPO underpricing in Chinese A-share market. After considering the specific characteristics of China's stock market and investigates whether the traditional theories of developed countries are applicable to the underpricing of IPO in China. Through the empirical analysis, the results indicate that information asymmetry theory, investor behavior, and time intervals can all be used to explain the IPO underpricing in the Chinese market. Despite the high degree of IPO underpricing, the situation has improved after reforms.